Sedulang Setudung Dance Learning using the Peer Tutor Method in Extracurricular Activities at SMK Unggul Negeri 2 Banyuasin Regency - Audian, Dwiky Dandy; Yelli, Nofroza; Ilhaq, Muhsin (Jurnal Pendidikan Amartha, 2022)
TLearning Sedulang Setudung Dance Using the Peer Tutor Method in Extracurricular Activities at State Vocational High School 2 Banyuasin Regency. The formulation of the problem in this study is "How is the Learning of Sedulang Setudung Dance Using the Peer Tutor Method in Extracurricular Activities at State Vocational High School 2 District. From these problems, the purpose of this research is to find out the Learning of Sedulang Setudung Dance Using the Peer Tutor Method in Extracurricular Activities at SMK Unggul Negeri 2 Banyuasin Regency. The research method used in this study is a qualitative descriptive method. The object of this research is learning extracurricular dance at SMK Unggul Negeri 2 Banyuasin Regency. Data collection techniques used in this study are observation techniques, interview techniques and documentation techniques. From the results of research data that has been carried out by researchers through observation data, interview data and documentation data, it shows that the learning process of Sedulang Setudung Dance in dance extracurricular activities at SMK Unggul Negeri 2 Banyuasin goes well, students can achieve completeness in learning at the time of evaluation or evaluation. assessment of the practice of Sedulang Setudung Dance. Trainers in dance extracurricular activities always provide learning that makes students excited. although the lack of facilities such as the absence of a special room for dance and media in the learning process, it does not reduce the enthusiasm of students in participating in teaching and learning activities.